2017
DOI: 10.1007/s40268-017-0174-z
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Risk Factors for Virological Outcome of Raltegravir-Based Therapy for Treatment-Experienced HIV-Infected Patients

Abstract: ObjectiveWe evaluated the effectiveness of a raltegravir (RAL)-containing regimen plus an optimized background regimen in HIV-1 highly treatment-experienced patients.DesignA retrospective cohort, multicentre study was conducted.MethodsAdult (>16 years old) HIV treatment-experience patients starting therapy with a RAL-containing regimen were included. Effectiveness was evaluated as the percentage of patients with an undetectable HIV-1 RNA viral load (<50 and <200 copies/mL) after 48 weeks, and changes in CD4+ c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
6
0
2
Order By: Relevance
“…Phase 3 trials showed that baseline plasma HIV-RNA did not affect DTG-based therapy; for raltegravir, the impact of baseline viral load is discussed controversially [ 8 , 11 ]. Smaller clinical studies that encompassed drug-naive and treatment-experienced patients suggested that older age [ 12 , 13 ], lack of adherence [ 14 ], origin from a high-prevalence country, injection drug use, and a low CD4 count at baseline [ 13 ] increased the risk for failure of InSTI-based therapy.…”
mentioning
confidence: 99%
“…Phase 3 trials showed that baseline plasma HIV-RNA did not affect DTG-based therapy; for raltegravir, the impact of baseline viral load is discussed controversially [ 8 , 11 ]. Smaller clinical studies that encompassed drug-naive and treatment-experienced patients suggested that older age [ 12 , 13 ], lack of adherence [ 14 ], origin from a high-prevalence country, injection drug use, and a low CD4 count at baseline [ 13 ] increased the risk for failure of InSTI-based therapy.…”
mentioning
confidence: 99%
“…Los esquemas de TARGA basados en Raltegravir incluidos en el estudio presentan un importante efecto antirretroviral, que se refleja en la importante reducción de la carga viral a los 6 meses de tratamiento. En concordancia, diversos estudios que han evaluado la eficacia de los esquemas basados en este medicamento en condiciones clínicas reales han demostrado una alta eficacia para el control del virus (4,6,7) . Sin embargo, los datos siguen siendo aún limitados, sobre todo, en nuestra población (8) .…”
Section: Discussionunclassified
“…Se encontraron altas tasas de supresión virológicas a las 48 semanas de tratamiento similares al nuestro. Por otro lado, la edad mayor de 40 años se asoció a un buen resultado virológico con importante tamaño del efecto (Odds Ratio [OR]: 5,61; Intervalo de confianza al 95% [IC-95%]: 1,61-18,84), sin embargo, el uso de Tenofovir dentro del régimen se asoció a un mal resultado virológico (OR:0,16; IC-95%: 0,03-0,80) (7) .…”
Section: Discussionunclassified
“…6,7 Patients in our study who had previously failed several regimens, including potent ones initiated in recent years, may have been non-adherent to the new INSTI-based treatment. Two observational studies reporting 48-week outcomes of switching from a failing regimen to RAL found failure rates of 15% and 35%, 17,24 while another two studies found a failure rate of 20% at 24 weeks. 18,25 Only one study of RAL reported high suppression rates after 2 years in patients switching from a failing regimen.…”
Section: Discussionmentioning
confidence: 99%